An unusual presentation of garre’s osteomyelitis of mandible: A case report - Samanta, Debraj; Sahu, Sudipta; Banerjee, Rajarshi; Mandal , Sayan; Mishra, Mayukh; Roy, Suranjana (Journal of Orofacial Research, 2024)
Chronic non-suppurative osteomyelitis, also known as Garre’s osteomyelitis is a local thickening of periosteum caused by slight irritation or infection. Here, we present the case report of a unilateral bony swelling in the left side of the lower jaw associated with an infection in an 8-year-old child. The radiograph revealed the pathognomic feature of ‘onion skin’ appearance. Surgical recontouring of the lower jaw was performed since there was no evidence of bone remodelling after the removal of granulation tissues.